Risk-chasing behaviour in on-site construction decisions. Issue 12 (1st December 2016) - Fiolet, Jean-Charles; Haas, Carl; Hipel, Keith
Abstract : Risk-chasing behaviour in on-site construction decision-making can result in illogical decisions and, thus, significant project losses. Accordingly, the authors conducted a set of experiments in order to detect the existence of such behaviour under a range of typical project conditions within a set of common situations. Fifty-three project leaders participated in the experiments by making choices framed by a set of 24 questions. Each question related to a known behavioural tendency, included the influence of an external parameter, and contained information from which expected values could be derived. Participants were well distributed by geography, age and experience. Contrary to the common perception that construction decision-makers are relentlessly risk-averse, they demonstrated risk-chasing behaviour when the decision occurred in over-budget project conditions. Younger participants were even more risk chasing in such conditions. Understanding and identifying where such behaviour occurs could ultimately lead to the development of means of avoiding the resulting losses.